Engineered zinc‐finger nuclease to generate site‐directed modification in the KLF1 gene for fetal hemoglobin induction. Issue 5 (16th December 2018) - Shariati, Laleh; Modarressi, Mohammad Hossein; Tabatabaiefar, Mohammad Amin; Kouhpayeh, Shirin; Hejazi, Zahra; Shahbazi, Mansoureh; Sabzehei, Faezeh; Salehi, Mansoor; Khanahmad, Hossein
Abstract: Elevation of hemoglobin F (HbF) ameliorates symptoms of β‐thalassemia, as a common autosomal recessive disorder. In this study, the ability of an engineered zinc‐finger nuclease (ZFN) system was assesed to disrupt the KLF1 gene to inhibit the γ to β hemoglobin switching in K562 cells. This study was performed using a second generation integration‐deficient lentiviral vector assigned to transient gene targeting. The sequences coding for zinc finger protein arrays were designed and subcloned in TDH plus as a transfer vector. Transduction of K562 cells was performed with the integrase minus lentivirus containing ZFN. The indel percentage of the transducted cells with lentivirus containing ZFN was about 29%. Differentiation of K562 cell line into erythroid cell lineage was induced with cisplatin concentration of 15 µg/mL. After differentiation, γ‐globin and HbF expression were evaluated using real‐time reverse‐transcription polymerase chain reaction and hemoglobin electrophoresis methods. The levels of γ‐globin messenger RNA were nine‐fold higher in the ZFN treated cells compared with untreated cells 5 days after differentiation. Hemoglobin electrophoresis method showed the same results for HbF level measurement. Application of the ZFN tool to induce KLF1 gene mutation in adult erythroid progenitors might be a candidate to stimulate HbF expression in β‐thalassemia patients. Abstract : The present study was performed to study the ability of an engineered zinc‐finger nuclease (ZFN), to make disruption in KLF1 and obstruct process of switching to γ‐globin elevation.